Improvement of 3D printed pure copper (Cu) surface properties using planar ultrasonic rolling
The processing of 3D printed pure copper workpieces through planar ultrasonic rolling technology solves the problems of low density and insufficient strength of parts, realizes surface defect enclosure, tissue refinement and performance improvement, and is suitable for applications under high mechanical loads and high temperature conditions. .
Patent Information
- Application Number
- CN202411588294.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
3D printed pure copper parts have problems such as low density, high shrinkage, high gap rate, limited strength and surface integrity, which limits their application under high mechanical loads and high temperature conditions.
Planar ultrasonic rolling technology is used to process 3D printed pure copper workpieces. Through the combination of ultrasonic high-frequency vibration and static load rolling, surface defects are eliminated, microscopic pores and cracks are closed, tissue is refined, and surface density and hardness are improved.
It effectively improves the density, strength and surface integrity of 3D printed pure copper surfaces, reduces surface roughness, improves microhardness and fatigue resistance, and enhances the application performance of parts.
Smart Images

Figure CN119426615A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal surface treatment, and in particular to a method for improving the surface properties of 3D-printed pure copper (Cu) by using planar ultrasonic rolling. Background Art
[0002] 3D printing technology, also known as additive manufacturing (AM), is an important component of the digitalization, intelligence and informatization of the manufacturing industry. It integrates computer-aided design, material processing and forming technology. It is based on the 3D model designed by the computer. Through digital system control, it uses laser beams, hot melt nozzles and other methods to stack and fuse metal powder, ceramic powder, plastic and other special materials prepared in advance layer by layer, and finally stack and form them to produce personalized and customized physical products. AM technology has the advantages of forming complex structures, high material utilization, and no need for molds. It has great application potential in the preparation of pure copper and copper alloy radiators, exchangers, tail nozzles, motor windings and other parts with complex integrated functions.
[0003] Electron beam melting (EBM) is a type of AM technology that uses a high-energy electron beam to selectively melt metal powder particles and locally fuse them with the previous cladding layer. The repeated process allows components to be built layer by layer. It is a mainstream AM technology with development prospects. In the process of preparing pure copper using EBM technology, since the high thermal conductivity of copper will affect the stability of interlayer fusion, controlling the appropriate electron beam energy density is the basis for selective electron beam melting and electron beam metal melting of copper and copper alloys, and it is also the difficulty in regulating the organization and improving the performance of formed parts; binder jetting technology can solve the problem of poor interlayer fusion stability caused by the high thermal conductivity of copper, and successfully realize the 3D printing of pure copper and copper alloys, but there are still problems such as low density, large shrinkage, high gap rate, limited strength and surface integrity. Therefore, its large-scale engineering application as a structural material is limited and cannot meet the engineering use requirements of such materials.
[0004] AM technology can make pure copper and copper alloy parts more complex, refined, lightweight and integrated, so that pure copper and copper alloy parts have good electrical and thermal conductivity while meeting the requirements of complex shapes and structures to achieve the expected service effect. However, the inherent low strength of pure copper at room temperature and its inability to resist thermal softening limit the application of 3D printed pure copper parts under high mechanical loads and high temperature conditions. Its thermal conductivity and electrical conductivity will drop significantly in certain high temperature environments. In order to better use 3D printed pure copper, it is still necessary to study how to further improve the service performance of 3D printed pure copper, such as forming process, microstructure, mechanical properties, etc.
[0005] The products obtained by existing metal 3D printing technology are prone to defects such as holes, looseness, and unmelted materials, which will lead to problems such as poor density, low strength and hardness, poor wear resistance, and insufficient fatigue resistance, limiting their performance. It is urgent to design a surface modification method for 3D printed metal workpieces to solve these problems. Summary of the invention
[0006] The object of the present invention is to provide a method for improving the surface properties of 3D-printed pure copper (Cu) by plane ultrasonic rolling, so as to solve the above-mentioned problems in the background technology. The present invention uses ultrasonic plane rolling technology to eliminate the defects introduced by additive manufacturing in the surface layer, close the defects and holes in the surface layer, reduce the surface roughness, and refine the structure. Through the ultrasonic high-frequency vibration and static rolling of ultrasonic plane rolling technology, the density of the surface modification layer of the material can be increased, and the microscopic pores and cracks in the surface modification layer of the material can be effectively closed, reducing the presence of microscopic defects. USRP treatment can achieve microstructure refinement and dislocation proliferation, thereby improving microhardness.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a method for improving the surface properties of 3D printed pure copper by plane ultrasonic rolling, comprising the following steps:
[0009] The 3D printed pure copper workpiece is fixed with a fixture and processed using an ultrasonic surface rolling process.
[0010] Preferably, the 3D printed pure copper workpiece is an electron beam selective melting 3D printed pure copper workpiece.
[0011] Preferably, the fixture is a loading platform with a solid support at the bottom.
[0012] The fixture used in the present invention is a solid supporting stage with a movable clamp to fix the sample, so that the sample can be attached to the fixture, avoiding problems such as uneven force and unclear pressure effect caused by the sample being suspended in the air.
[0013] Preferably, the static pressure of the ultrasonic surface rolling process is 0.1-0.3 MPa, the pressing amount is 50 μm, the frequency is 50 Hz, and the speed is 2000 mm / rev.
[0014] The second technical solution of the present invention is to provide a surface-modified 3D printed pure copper workpiece prepared according to the above method.
[0015] The technical principles of the present invention are as follows:
[0016] Among the current surface treatment processes, surface severe plastic deformation (SSPD) can achieve excellent grain refinement without excessively changing the original dimensions of the component, making it particularly suitable for various metal materials. As a new SSPD technology, ultrasonic surface rolling process (USRP) integrates surface mechanical rolling treatment, deep rolling and ultrasonic shot peening. It converts the alternating current generated by the ultrasonic device into mechanical vibration of the same frequency and applies pulsating force to the sample surface through the processing tip. In this process, a rolling carbide ball is used as the USRP tip and lubricating oil is introduced to the interface between the tip and the sample surface. With the assistance of the control machine, the USRP device can achieve precise control of the vibration intensity and density, thereby ensuring the repeatability of the process, and has the advantages of no chipping, no pollution, low cost, high efficiency and good compatibility.
[0017] Ultrasonic surface rolling process (USRP) is a surface strengthening process that combines ultrasonic vibration impact and continuous rolling. Its advantage is that it can make the metal surface obtain sufficient pressure layer depth while maintaining the original surface characteristics of the material. This process applies ultrasonic vibration of a given frequency to the surface of the component through the processing tool head, and uses the rolling tool head (given feed speed) as a carrier to transmit static rolling and ultrasonic impact to the surface of the component, forcing plastic deformation to occur within the range stress field formed on the surface of the material. Such repeated operations make the plastic deformation act on different positions of the processed parts, thereby refining the surface grains and reducing the surface roughness to the nanometer level. After the processing is completed, the workpiece will also produce a certain elastic recovery, and the plastic flow generated by it will balance the "valley", "quilt" and "peak" on the surface of the component, further reducing its surface roughness. USRP can effectively reduce or even eliminate the surface defects caused by repeated processing by adjusting the parameters in the processing; at the same time, the surface plastic deformation caused by repeated high-frequency ultrasonic vibration of this process can enable the processed parts to obtain good surface comprehensive performance indicators. Due to the presence of ultrasonic vibration, rolling can have a greater impact on the metal surface under a very small amount of static pressure, further introducing greater plastic deformation and residual compressive stress on the surface of the parts, and causing the surface structure of the parts to be refined. The surface structure of the parts can obtain gradient distribution characteristics after ultrasonic rolling. USRP can improve the surface finish, reduce the roughness of the machined surface, refine the surface grains, increase the surface hardness, thereby obtaining a gradient change in hardness, and introduce residual stress on the surface, which can improve the fatigue resistance and wear resistance of the parts, so that the metal surface can obtain excellent performance and optimize its related application service effects.
[0018] 3D printed pure copper is different from copper-based printed alloys. The alloying elements in copper-based printed alloys can increase the nucleation sites and reduce printing defects. However, 3D printed pure copper has more serious defects and holes than copper-based printed alloys, which will seriously affect its service effect.
[0019] The beneficial technical effects of the present invention are as follows:
[0020] The present invention uses ultrasonic flat rolling technology to eliminate defects in the surface layer introduced by additive manufacturing, close defects and holes in the surface layer, reduce surface roughness, and refine the structure.
[0021] Through the ultrasonic high-frequency vibration and static rolling of ultrasonic plane rolling technology, the density of the surface modification layer of the material can be increased, the microscopic pores and cracks in the surface modification layer of the material can be effectively closed, and the existence of microscopic defects can be reduced. USRP treatment can achieve microstructure refinement and dislocation proliferation, thereby improving microhardness.
[0022] The 3D printed pure copper surface modification scheme of the present invention can not only improve the surface integrity of the workpiece, but also has a certain improvement effect on the conductive properties of the workpiece. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The surface morphology, SEM images and density test results of U0, U1, U2 and U3. Among them, (a) and (a1) are the surface morphology and SEM images of U0; (b) and (b1) are the surface morphology and SEM images of U1; (c) and (c1) are the surface morphology and SEM images of U2; (d) and (d1) are the surface morphology and SEM images of U3; (e) is the density test result of U0, U1, U2 and U3.
[0025] Figure 2 (a) and (b) are cross-sectional morphologies of U0 at different locations.
[0026] Figure 3 The cross-sectional morphology of U1, U2 and U3. (a) is U1, (b) is U2 and (c) is U3.
[0027] Figure 4 Gradient hardness distribution (a) and surface microhardness (b) of U0, U1, U2, and U3.
[0028] Figure 5 Friction coefficient curves of U0, U1, U2, and U3.
[0029] Figure 6 The three-dimensional topographic maps (ad) and wear rate changes (e) of the friction and wear tests of U0, U1, U2, and U3. Among them, (a) is the three-dimensional topographic map of U0; (b) is the three-dimensional topographic map of U1; (c) is the three-dimensional topographic map of U2; (d) is the three-dimensional topographic map of U3.
[0030] Figure 7 It is a schematic diagram of the structure of the planar ultrasonic rolling equipment in Examples 1-3.
[0031] Figure 8 This is a macroscopic physical picture of U0 in the present invention.
[0032] Fig. 9 Schematic diagram of the preparation process of electron beam selective melting 3D printing pure copper. DETAILED DESCRIPTION
[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0037] The ultrasonic surface rolling process (USRP) is used to introduce gradient tissue on the surface of electron beam selectively melted 3D printed pure copper (EBMed-Cu). Scanning electron microscope (SEM), laser confocal microscope, Vickers hardness tester and friction and wear test are used to observe the microstructure and analyze the tribological properties of the samples after USRP treatment. The influence of different static pressure parameters of USRP treatment on the microstructure and properties of EBMed-Cu is explored, and the influence of the surface gradient layer on the surface integrity and tribological properties of EBMed-Cu is studied, so as to provide a theoretical basis for improving the surface properties of EBMed-Cu and provide a new solution for the difficulty of popularizing and applying EBMed-Cu parts in complex and harsh environments such as high friction and wear.
[0038] The preparation method of electron beam selective melting 3D printed pure copper (EBMed-Cu) used in the following embodiments and comparative examples of the present invention is shown in Fig. 9 .
[0039] Fig. 9 Schematic diagram of the preparation process of electron beam selective melting 3D printing pure copper.
[0040] The printing parameters are: speed parameter 6, reference current 7mA, beam spot size 25mA, line spacing 0.2mm, layer thickness 50μm. In addition, each process in the flowchart is briefly described as follows:
[0041] Recycle: Recycle the metal powder not used in the printing process, and add it during the process if necessary;
[0042] Sieving: The recovered and added metal powders are concentrated for sieving;
[0043] Printing: Add the sieved metal powder into the printer for printing;
[0044] Cooling: After printing, the workpiece is cooled along with the equipment;
[0045] Post-treatment: Remove the support of the printed part.
[0046] Since 3D printed pure copper is prone to obvious defects such as holes, which will seriously affect its service effect and cause harm to the safety of the service environment, the present invention cuts the EBMed-Cu sample into a cubic shape, clamps it on a stage with a solid support at the bottom, and then performs ultrasonic rolling treatment with different static pressure parameters. The surface integrity and tribological properties of the treated sample are characterized, in order to provide a certain reference value for the practical application of 3D printed pure copper.
[0047] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0048] Example 1
[0049] A method for improving the surface properties of pure copper (Cu) printed by 3D printing using planar ultrasonic rolling:
[0050] The electron beam selective melting 3D printed pure copper (denoted as U0) was fixed on a stage with a solid support at the bottom and processed using the ultrasonic surface rolling process (USRP); the parameters of the ultrasonic surface rolling process were: static pressure 0.1MPa, downward pressure 50μm, frequency 30Hz, speed 2000mm / rev. The obtained product was denoted as U1.
[0051] Example 2
[0052] The only difference from Example 1 is that the static pressure of USRP is modified to 0.2 MPa, and the obtained product is recorded as U2.
[0053] Example 3
[0054] The only difference from Example 1 is that the static pressure of USRP is modified to 0.3 MPa, and the obtained product is recorded as U3.
[0055] Effect verification
[0056] (1) The products of Examples 1-3 and U0 were cut, mounted, ground, polished, and etched, and then their organizational structure and surface morphology were observed using a Leica metallographic microscope and a scanning electron microscope. Figure 1-3 shown.
[0057] Figure 1 The surface morphology, SEM images and density test results of U0, U1, U2 and U3. Among them, (a) and (a1) are the surface morphology and SEM images of U0; (b) and (b1) are the surface morphology and SEM images of U1; (c) and (c1) are the surface morphology and SEM images of U2; (d) and (d1) are the surface morphology and SEM images of U3; (e) is the density test result of U0, U1, U2 and U3.
[0058] Depend on Figure 1 It can be seen that the surface of the U0 sample has obvious looseness, holes and other defects. After USRP treatment, the surface of the U1 and U2 samples becomes relatively smooth, without obvious defects, and only a small number of tiny pores, indicating that although the plastic flow of the material produced by USRP treatment can balance or reduce the surface defects of the sample, it cannot completely eliminate the defects. Although the number of pores on the surface of the U3 sample is more than that of the U1 and U2 samples, it is also greatly improved compared with the U0 sample. This is due to the high-frequency vibration of the ultrasonic wave and the static rolling effect, which increases the density of the surface modification layer of the material. In addition, compared with the untreated sample, the USRP treatment can effectively close the microscopic pores and cracks in the surface modification layer of the material and reduce the presence of microscopic defects.
[0059] Figure 2 (a) and (b) are cross-sectional morphologies of U0 at different locations.
[0060] from Figure 2 It can be observed that there are obvious pits on the surface of the U0 substrate, which is consistent with Figure 1 The pits appearing in (a1) are consistent with those in the figure, and the cross section shows a long and coarse lamellar grain structure, and there are also a large number of obvious defects.
[0061] Figure 3 The cross-sectional morphology of U1, U2 and U3. (a) is U1, (b) is U2 and (c) is U3.
[0062] Figure 3 In the figure, the cross-section of the sample after USRP treatment obviously has elongated and refined grain structure, among which the deformation depth of the gradient microstructure reached by the U1 sample is about 228μm. With the increase of the static pressure of USRP treatment, the deformation depth of the gradient microstructure reaches about 241μm in the U2 sample and about 253μm in the U3 sample. This shows that the USRP treatment introduces a gradient microstructure on the EBMed-Cu surface, including elongated grains, ultrafine grains, refined grains, and low-strain matrix in the EBMed-Cu sample due to dislocation movement.
[0063] (2) The changes in microhardness were measured using a Vickers hardness tester to discuss the effect of USRP treatment on the mechanical properties of 3D printed pure copper. Figure 4 shown.
[0064] Figure 4 Gradient hardness distribution (a) and surface microhardness (b) of U0, U1, U2, and U3.
[0065] from Figure 4As can be seen from (b), the surface hardness of the U0 sample without USRP treatment is about 57.49HV; after USRP treatment at a static pressure of 0.1MPa, the hardness of the U1 sample is significantly increased to 88.97HV, which is about 54.76% higher than that of the U0 sample; when the static pressure reaches 0.2MPa, the surface microhardness of the sample is increased to 94.51HV, which is about 64.39% higher than that of the U0 sample; for the U3 sample, the surface hardness reaches 99.82HV, which is about 73.63% higher than that of the U0 sample. In addition, Figure 4 As shown in (a), the gradient microhardness increases with the increase of the static pressure of USRP treatment. The depth of the work-hardened layer of the U1 sample is about 950μm, and the U2 and U3 samples have the deepest work-hardened layer (about 1250μm), which is 31.58% higher than that of the U1 sample.
[0066] The above results show that after USRP treatment, the microhardness value of the sample surface increases significantly and is much greater than the hardness of the unreinforced surface U0. Ultrasonic rolling is a gradual penetration process, and the surface strengthening layer formed is a gradual transition. As the depth from the surface gradually increases, the microhardness decreases and is basically the same as the original hardness of the material at the core of the specimen. The improvement in microhardness caused by USRP treatment can be attributed to the combined effect of microstructure refinement and dislocation proliferation. For USRP samples, the depth of the surface work-hardened layer is greater than Figure 3 The thickness of the plastic deformation layer is deep. The main reasons for this phenomenon are as follows: First, Figure 3 In the internal area near the boundary of the deformation zone and the undeformed zone, there are still some dislocation entanglements and dislocation walls, which lead to the increase of microhardness; secondly, there is a good correspondence between the degree of plastic deformation and the degree of increase of microhardness, that is, the greater the static pressure, the greater the degree of plastic deformation, the thicker the surface work-hardening layer, and the higher the surface microhardness.
[0067] (3) Friction coefficient is an important indicator for evaluating the tribological properties of materials, and it is related to the quality of the transmission and braking functions of the components. The samples were subjected to friction and wear tests to analyze the changes in their tribological properties. Laser confocal analysis was performed on the rolling surface of the samples and the wear scars after the friction and wear tests to observe their surface morphology and measure the surface roughness and wear scar volume. The coefficient of friction (COF) curves of the untreated and USRP-treated samples in the friction and wear test are shown in Figure 2. Figure 5 shown.
[0068] Figure 5 Friction coefficient curves of U0, U1, U2, and U3.
[0069] Figure 5In the case of the sample without USRP treatment (U0), the COF value steady-state level is about 0.88, and its COF value fluctuates greatly, undergoes a rapid initial increase, and then shows three different peaks, the first peak is higher than the second peak, COF reaches the highest value and then gradually decreases, and after a small range of changes, the third peak appears again, which is lower than the first two peaks; U1 and U2 samples show relatively constant COF values, with an average value of about 0.27, which is about 69.32% lower than that of U0 sample; In addition, for U3 sample, the initial peak value slightly decreases to a stable state with an average value of about 0.33, and the COF value reaches a maximum of 0.44, but it always remains lower than the COF value of U0 sample. In short, after USRP treatment, for U1, U2 and U3 samples, the COF values are greatly reduced, and the curve changes tend to be gentle. However, it is worth noting that the changes in two peaks of U3 sample and U0 sample are similar (the initial peak of U3 sample and the initial peak of U0 sample, the second peak of U3 sample and the third peak of U0 sample). From the perspective of the wave peaks, the former is mainly attributed to the surface morphology of the prepared samples. The Si3N4 grinding balls contact the abnormally uneven surfaces of the U0 and U3 samples, resulting in a prominent peak in the initial stage of friction; while the latter gradually decreases in the COF peak, and then a sudden peak appears again in the subsequent flat stage, and finally reaches a relatively stable state in the prepared samples. From the perspective of different USRP-treated samples, as for U0, due to the influence of the current metal 3D copper printing technology, the inevitable defects of the sample itself and the lower hardness lead to the above changes; as for the U3 sample, under the static pressure parameters of 0.1MPa and 0.2MPa, the COF curves of the U1 and U2 samples are relatively stable, while under the static pressure parameter of 0.3MPa, the above changes occur, which may be caused by the micro cracks and defects under the gradient layer caused by excessive rolling.
[0070] Another measure of the friction performance of the sample is the wear rate. The wear rate can be calculated based on the worn sample. The specific wear rate is calculated based on the Archard wear relationship, and the formula is as follows:
[0071]
[0072] Where K is the specific wear rate (mm 3 / N·m), V is the wear volume (mm 3 ), F is the load (N), and D is the wear distance (m).
[0073] Figure 6 The three-dimensional topographic maps (ad) and wear rate changes (e) of the friction and wear tests of U0, U1, U2, and U3. Among them, (a) is the three-dimensional topographic map of U0; (b) is the three-dimensional topographic map of U1; (c) is the three-dimensional topographic map of U2; (d) is the three-dimensional topographic map of U3.
[0074] Figure 6 It can be seen that the wear rate of the U0 sample is 2.16 mm 3 / N·m, the wear rate of U1 sample is 0.53mm 3 / N·m, which is 75.46% lower than that of U0; the wear rate of U2 sample is 0.51mm 3 / N·m, which is 76.39% lower than that of U0; while the wear rate of U3 sample is 0.45mm 3 / N·m, which is 79.17% lower than that of U0. It can be seen that the wear rate of the sample after USRP treatment is significantly reduced in comparison. The changes in COF and wear rate are mainly related to the different surface integrity after USRP treatment. In the present invention, the wear rate of EBMed-Cu treated with USRP is reduced by about 76.85% on average compared with the untreated sample, and the wear resistance is significantly improved.
[0075] Figure 7 It is a schematic diagram of the structure of the planar ultrasonic rolling equipment in Examples 1-3.
[0076] Figure 7 It can be seen that the ultrasonic rolling equipment uses static pressure and sinusoidal current to act on the rolling head in a coordinated manner, and then introduces lubricating oil into the rolling head, which is programmed to move on the sample, thereby achieving the purpose of improving the surface properties of the sample. The fixture for fixing the sample uses a stage with a solid support at the bottom, so that the sample is evenly stressed during the rolling process, avoiding tissue differences caused by uneven stress; the movable clamp of this fixture can fix samples of various sizes.
[0077] Figure 8 This is a macroscopic physical picture of U0 in the present invention.
[0078] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for improving the surface properties of 3D printed pure copper by plane ultrasonic rolling, characterized in that: The following steps are involved: The 3D printed pure copper workpiece is fixed with a fixture and processed using an ultrasonic surface rolling process.
2. The method according to claim 1, characterized in that The 3D printed pure copper workpiece is an electron beam selective melting 3D printed pure copper workpiece.
3. The method according to claim 1, characterized in that The fixture is a loading platform with a solid support at the bottom.
4. The method according to claim 1, characterized in that: The static pressure of the ultrasonic surface rolling process is 0.1-0.3 MPa, the pressing amount is 50 μm, the frequency is 30 Hz, and the speed is 2000 mm / rev.
5. A surface-modified 3D printed pure copper workpiece prepared according to the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Metal component optimization method based on additive process forming and forming equipment with same
CN109158829A
Remanufacturing method and device for H13 die steel
CN112795918A
Method for ultrasonic rolling surface strengthening laser additive manufacturing of eutectic high-entropy alloy plate
CN114682800A